Empowerment, Training, and Development of Human Resources in Tourism Areas Jl. Asia Africa Bandung to Optimize Potency Tourist and Economy Creative in City Bandung - Priyana, Indarta; Purwadisastra, Dikdik (Jurnal Mamangan, 2023)
Tourism in the city of Bandung has enormous potential for economic growth Bandung, tourism in the city of Bandung is an urban tour with many choices of destinations tour among them area Road Asia Africa City Bandung which famous with building historic sites and shopping centers, the problem of inconvenience for tourists is a challenge itself for the Bandung City Government to increase tourism actors in the area, This study aims to examine training patterns, inhibiting factors and implementation of policies in improving the quality of Human Resources in Jalan Asia area Africa, Method study which used Qualitative with approach descriptive, results research it is known that there has been no training and development for Source of Power Man perpetrator tour area Road Asia Africa City Bandung, recommendation stingray researcher The pentahelix concept is collaboration between stakeholders or across institutions must each other synergize Among Government City Bandung with stakeholders good with organization Public, College Tall nor institution institution different.